Carl Harms papers - Harms, Carl, 1910-
Daily journal kept by Harms as the cartographer and cook on an expedition to the Galapagos Islands sponsored by the U.S. Navy and the Pacific Development Company to select a site for a military base. Also includes a guidebook, newsletters, scrapbook, map, and photograph.
Sailor. Full name: H. Carl Harms.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Pacific Development Company; Military bases, American; World War, 1939-1945 -- Pacific Ocean; Galapagos Islands -- Description and travel; Sailors